A unilateral 3D indoor positioning system employing optical camera communications - Younus, Othman Isam; Chaudhary, Neha; Ghassemlooy, Zabih; Alves, Luis Nero; Zvanovec, Stanislav; Pattas, Dimitrios; Papanikolaou, Vasilis K. (IET Optoelectronics, 2023)
This article investigates the use of a visible light positioning system in an indoor environment to provide a three dimensional (3D) high-accuracy solution. The proposed system leveraged the use of a single light-emitting diode and an image sensor at the transmitter and the receiver (Rx) respectively. The proposed system can retrieve the 3D coordinate of the Rx using a combination of the angle of arrival and received signal strength (RSS). To mitigate the error induced by the lens at the Rx, a novel method is proposed and experimentally tested. The authors show that, the proposed method outperforms previously reported RSS under all circumstances and it is immune to varying exposure times within the standard range of 250 µs to 4 ms. The authors experimentally demonstrate that the proposed algorithm can achieve a 3D root mean squared error of 7.56 cm.
Created from Fastlane, Scopus look-up
Keywords: cameras; LED lamps; optical communication